2023
DOI: 10.1111/nph.18727
|View full text |Cite
|
Sign up to set email alerts
|

A rust‐fungus Nudix hydrolase effector decaps mRNAin vitro and interferes with plant immune pathways

Abstract: To infect plants, pathogenic fungi secrete small proteins called effectors. Here, we describe the catalytic activity and potential virulence function of the Nudix hydrolase effector AvrM14 from the flax rust fungus (Melampsora lini).We completed extensive in vitro assays to characterise the enzymatic activity of the AvrM14 effector. Additionally, we used in planta transient expression of wild-type and catalytically dead AvrM14 versions followed by biochemical assays, phenotypic analysis and RNA sequencing to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…2G). Conversely, AvrM14, a sequence-unrelated mRNA decapping Nudix hydrolase effector from the fungus Melampsora lini (30), does not hydrolyze 5-PP-InsP5 (fig S5D).…”
Section: Magnaporthe and Colletotrichum Nudix Effectors Are Diphospho...mentioning
confidence: 99%
See 1 more Smart Citation
“…2G). Conversely, AvrM14, a sequence-unrelated mRNA decapping Nudix hydrolase effector from the fungus Melampsora lini (30), does not hydrolyze 5-PP-InsP5 (fig S5D).…”
Section: Magnaporthe and Colletotrichum Nudix Effectors Are Diphospho...mentioning
confidence: 99%
“…2G). Conversely, AvrM14, a sequence-unrelated mRNA decapping Nudix hydrolase effector from the fungus Melampsora lini ( 30 ), does not hydrolyze 5-PP-InsP 5 (fig S5D). All Nudix effectors used throughout this study were purified to homogeneity prior to in vitro characterization (fig.…”
Section: Main Textmentioning
confidence: 99%
“…3′-NADP + was previously only reported as a synthetic inhibitor of NAD + -dependent enzymes ( 23 ). A NUDIX hydrolase virulence protein called AvrM14 from a fungal plant pathogen can interfere with host NAD + -capping of mRNA, potentially to posttranscriptionally regulate gene expression ( 24 ). The other NADase families discovered by Hulin et al.…”
Section: Nad + As a Common Target For Diverse Viru...mentioning
confidence: 99%
“…While many studies have identified and characterised a diverse array of molecular functions for such effectors, few have focussed on putative enzymatic activities as these are often not predicted from sequence or structure. A new paper published in this issue of New Phytologist by McCombe et al (2023; pp. 222-239), provides novel insight into the Nudix hydrolase effector AvrM14 from the flax rust fungus (Melampsora lini).…”
mentioning
confidence: 99%
“…A new paper published in this issue of New Phytologist by McCombe et al . (2023; pp. 222–239), provides novel insight into the Nudix hydrolase effector AvrM14 from the flax rust fungus ( Melampsora lini ).…”
mentioning
confidence: 99%